Cross Sectional Study: A Five Year Review Of Gestational Trophoblastic Disease In Kuantan General Hospital (Jan 1995 - Dec 1999) - Mohamed Jamli, Mohamad Faiz (2001)
To study the epidemiology, features, treatment of Gestational Trophoblastic Disease (GTD) and regression of serum BheG in Hydatidiform mole. To identify factors that predict the risk of developing Gestational Trophoblastic Tumour (GTT) from Hydatidiform mole and to compare the outcome of treatment between Gestational Trophoblastic Tumour (GTT) from known antecedent pregnancy (Hydatidiform mole) and unknown antecedent pregnancy.